Azaxanthones and azathioxanthones are effective sensitisers for europium and terbium luminescence. - Atkinson, P; Findlay, K; Kielar, F; Pal, R; Parker, D; Poole, R; Puschmann, H; Richardson, S; Stenson, P; Thompson, A; Yu, J (2006)
Several azaxanthone and azathioxanthone sensitising chromophores have been incorporated into macrocyclic ligands and form well-defined Eu and Tb complexes in polar media. Excitation of the heterocyclic chromophore in the range 330 to 382 nm leads to modest amounts of aromatic fluorescence and relatively efficient metal-based luminescence, with absolute metal-based quantum yields of up to 24% in aqueous media.